THU0062 Assessing inflammatory activity in rheumatoid arthritis and ankylosing spondylitis. serum amyloid a or c-reactive protein?. (1st June 2001) - Gómez, A; Sanmartí, R; Álvarez, L; Salvador, G; Cañete, JD; Filella, X; Gratacós, J; Muñoz-Gómez, J
Abstract : Background: Serum amyloid A (SAA) protein has been suggested to be a more sensitive marker of disease activity than CRP in rheumatoid arthritis (RA). Few studies are carried out in patients with ankylosing spondylitis (AS). Objectives: To analyse if SAA correlates with other markers of inflammatory activity such as CRP, ESR and serum levels of IL-6 in both RA and AS. To evaluate if SAA is the most sensitive marker of clinical disease activity in RA. Methods: Using a sensitive ELISA test (N-latex SA, Dadde Behring), SAA was measured in the serum of 51 patients with RA and 44 patients with AS. CRP, ESR and serum IL-6 (ELISA) were measured simultaneously. Clinical parameters of disease activity (number of painful and swollen joints) and Thompson's articular index were analysed also in RA patients. Results: The magnitude of the SSA response was greater than the CRP (x ± SD: SAA = 32.7 ± 56.7 mg/l vs CRP = 18.8 ± 26.3 mg/l p < 0.001). Patients with RA showed higher SAA levels than AS (x ± SD: 44.8 ± 64 mg/l vs 13.6 ± 18.9 mg/l p < 0.001). In both RA and AS, SAA correlates significantly with ESR (r = 0.51; p = 0.0001 in RA and r = 0.61; p = 0.0001 in AS), CRP (r = 0.70; p = 0.0001 in RA and r = 0.66; p = 0.0001 in AS) and IL-6 (r = 0.58 in RA; p = 0.0001, and r = 0.48 in AS; p = 0.001). In patients with RA, SAA but not CRP, ESR or IL-6, showed a positive, although weak correlation with the number of painful joints (r = 0.31; p = 0.03). Thompson articular index, but not the swollen joint count, correlates with the four parameters analysed; this correlation was better for CRP (r = 0.51; p = 0.0001) than for SAA (r = 0.39; p = 0.007) ESR (r = 0.35; p = 0.02) or IL-6 (r = 0.37; p = 0.01). Conclusion: In both RA and AS, SAA correlates well with other laboratory markers (mainly with CRP) of inflammation. However SAA is not a better marker of clinical disease activity than CRP in RA.